A Suprachoroidal Electrical Retinal Stimulator Design for Long-Term Animal Experiments and In Vivo Assessment of Its Feasibility and Biocompatibility in Rabbits. (14th February 2008) - Zhou, J. A.; Woo, S. J.; Park, S. I.; Kim, E. T.; Seo, J. M.; Chung, H.; Kim, S. J.
Abstract : This article reports on a retinal stimulation system for long-term use in animal electrical stimulation experiments. The presented system consisted of an implantable stimulator which provided continuous electrical stimulation, and an external component which provided preset stimulation patterns and power to the implanted stimulator via a paired radio frequency (RF) coil. A rechargeable internal battery and a parameter memory component were introduced to the implanted retinal stimulator. As a result, the external component was not necessary during the stimulation mode. The inductive coil pair was used to pass the parameter data and to recharge the battery. A switch circuit was used to separate the stimulation mode from the battery recharging mode. The implantable stimulator was implemented with IC chips and the electronics, except for the stimulation electrodes, were hermetically packaged in a biocompatible metal case. A polyimide-based gold electrode array was used. Surgical implantation into rabbits was performed to verify the functionality and safety of this newly designed system. The electrodes were implanted in the suprachoroidal space. Evoked cortical potentials were recorded during electrical stimulation of the retina. Long-term follow-up using OCT showed no chorioretinal abnormality after implantation of the electrodes.